Clinical aspect and management of basal cell carsinoma - Agus Supartoto, Agus Supartoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Objective: To identify the pattern, clinic:al aspect and management of Basal Cell Carsinoma (BCC) at Ophthalmology Department, Dr. Sardjito Hospital, Yogyakarta from 1997 to 2002.Methods: The author reviewed eligible medical records of all patients with BCC diagnosis based on clinical symptoms and histopatologic examination. Operative management with frozen section procedure. Results: Based on the collected data we found 31 cases of BCC in 1997 to 2002. Most of these cases (30) were noduloulcerative types, while 1 case was morphea in type. Most location of lesion were inferior palpebral region. In these cases, the range of age was between 49-75 years. Wide excision with skin graft was performed on 11 cases and 9 cases with orbital exenteration and skin graft, 6 cases with wide excision and skin flap, 5 cases orbital exenteration Ã¢â¬âwide excisionÃ¢â¬â skin graft, as well as the ensuring 17 cases with radiotherapy. Most of the cases (30 cases) were good at follow up with a period of follow up between 2-14 month, while 1 case died.Conclusions: The most frequent of BCC were ulcerative nodular type, most location in the inferior palpebral region. Wide excision and skin graft management in the majority of cases clinical good result.Key words: BCC-Noduloulcerative type- Wide excision and skin graft.